Potential of Small‐Angle Neutron Scattering for Evaluating Protein Locus within a Polymersome. Issue 1 (31st October 2022) - Palinske, Max; Muza, Upenyu L.; Moreno, Silvia; Appelhans, Dietmar; Boye, Susanne; Schweins, Ralf; Lederer, Albena
Abstract: Post‐loading of polymersomes with different bio(macro)molecules has been successfully demonstrated, thus mimicking the diffusion processes through biological membranes. However, it is still an open issue the extent to which this diffusion process leads to transmembrane transportation, or rather encapsulation of cargo within the membrane. In this study, well‐established pH‐responsive and cross‐linked polymeric vesicles are studied. A pH‐controllable and stable membrane, as well as a hollow particle shape and membrane uniformity are confirmed using dynamic light scattering (DLS) and cryogenic‐transmission electron microscopy (Cryo‐TEM). Post‐loading with myoglobin (Mb) as a model enzyme is analyzed using multidetector asymmetrical flow field‐flow fractionation (AF4). Advanced analysis of conformational parameters allowed for the estimation of enzyme localization and the pH‐dependent loading efficiency thereof. Static light scattering coupled to AF4 is employed to successfully deliver information on the global size of the polymersomes (>50 nm). Furthermore, membrane structure and thickness, which are in the few nanometer range, can be successfully analyzed using small‐angle neutron scattering (SANS). Deuterated solvent as well as Mb deuteration for tuning the contrast are considered. Two different vesicle model fits, as well as Kratky–Porod interpretation confirm effective determination of vesicle core and membrane thickness and for evaluation of the membrane changes after post‐loading. Abstract : Post‐loading of polymersomes with biomolecules mimics the diffusion processes through biological membranes. The cargo location and the membrane changes after loading are investigated using multidetector asymmetrical flow field‐flow fractionation, light scattering, and microscopy. A comparison with small‐angle neutron scattering shows that vesicle model fits, as well as Kratky–Porod interpretation, can be used to evaluate membrane changes after post‐loading.